Neonatal Tactile Stimulations Affect Genetic Generalized Epilepsy and Comorbid Depression-Like Behaviors - Balikci, Aymen; Ilbay, Gul; Ates, Nurbay (Frontiers in Behavioral Neuroscience, 2020)
Recent studies suggest that development of absence epilepsy and comorbid depression might be prevented by increased maternal care of the offspring, in which tactile stimulation induced by licking/grooming and non-nutritive contact seem to be crucial. In this study, we aimed to evaluate the effect of neonatal tactile stimulations (NTS) on absence epilepsy and depression-like behaviors in adulthood. Wistar Albino Glaxo from Rijswijk (WAG/Rij) rat pups with a genetic predisposition to absence epilepsy were divided into tactile stimulation (TS) group, deep touch pressure (DTP) group, maternal separation (MS) group or control group. Between postnatal day 3 and 21, manipulations (TS, DTP, and MS) were carried out for 15 minutes and three times a day. Animals were submitted to locomotor activity, sucrose consumption test (SCT) and forced swimming test (FST) at five months of age. At the age of six months, the electroencephalogram (EEG) recordings were conducted in order to quantify the spike-wave discharges (SWDs), which is the hallmark of absence epilepsy. The TS and DTP groups showed less and shorter SWDs in later life in comparison to maternally separated and control rats. SWDs’ number and total duration were significantly reduced in TS and DTP groups whereas mean duration of SWDs was reduced only in DTP group (p<0,05). TS and DTP also decreased depression-like behaviors measured by SCT and FST in adult animals. In the SCT, number of approaches was significantly higher in TS and DTP groups than the maternally separated and control rats. In the FST, while the immobility latency of TS and DTP groups was significantly higher, only TS group showed significantly decreased immobility and increased swimming time. The results showed that NTS decreases both the number and length of SWDs and the depression-like behaviors in WAG/Rij rats probably by increasing arousal level and causing alterations in the level of some neurotrophic factors as well as in functions of the neural plasticity in the developing rat’s brain.